The Implementation of Learning Management as an Effort to Improve Students’ Achievement at Elementary School - Budi Setiawan Ginting; Neliwati Neliwati; Elfin Nazri; Abdul Latif Hutagaol (Jurnal Basicedu, 2022)
This study aims to describe the implementation of learning management in SD IT Ad-Durrah Medan. This is done to analyze learning management as an effort to improve student achievement, both from aspects of planning, implementation, supervision, evaluation, to reporting. This study uses a qualitative approach with a descriptive study method. Observations were made at SD IT Ad-Durrah Medan from March to June 2022. The research subjects included teachers (homeroom teachers from grades 1-4 of SD), principals, vice principals and students. The validity of the data that has been obtained through interviews, observation and documentation was tested using data and source triangulation techniques. The results of this study conclude that (1) learning planning includes curriculum preparation, annual programs, semester programs, minimum completeness criteria (KKM), study time management, lesson plans, educational calendars and student quality improvement programs; (2) the implementation of learning includes preparation activities (perception), core activities (exploration, refinement and confirmation), and termination activities; (3) learning supervision includes internal supervision from the school principal on the process of providing education and improving the school's human resources (HR); and (4) learning evaluation includes pre-test, daily test, mid-semester exam (UTS) and final semester exam (UAS). Learning reports by teachers are documented in student report cards as a description of student learning outcomes.